Silver catalyzed gallium phosphide nanowires integrated on silicon and in situ Ag-alloying induced bandgap transition. (5th June 2015) - Huang, Kangrong; Zhang, Zhang; Zhou, Qingwei; Liu, Liwei; Zhang, Xiaoyan; Kang, Mengyang; Zhao, Fuli; Lu, Xubing; Gao, Xingsen; Liu, Junming
Abstract: In this work, we demonstrate a silver catalyzed heteroepitaxial growth of gallium phosphide nanowires (GaP NWs) on silicon. The morphology and growth direction of GaP NWs on differently orientated Si substrates were investigated. From crystallographic analysis, we inferred that Ag from catalyst is incorporated into the GaP during the chemical beam epitaxy (CBE) process. Using the PL spectrum and time-resolved emission spectroscopy, the optical properties of Ag-catalyzed GaP NWs were greatly modified, with bandgap transitions in the blue range. The Raman characterizations further confirmed the Ag incorporation into GaP during the growth. From the bandgap calculations, it was deduced that Ag was substituted on the Ga site with bandgap broadening. The in situ Ag-alloying during the growth of Ag-catalyzed GaP NWs greatly modified the band structure of GaP, and could lead to further applications in optoelectronics for low-dimensional GaP-based nanomaterials.